Characteristics of First Aid Types for Pelvic Trauma in Women Injured During Local Military Conflicts - V. V. Maslyakov; I. A. Salov; S. A. Sidelnikov; Yu. E. Barachevsky; A. V. Parshin; M. A. Polidanov (Неотложная медицинская помощь)
AIM OF STUDY. To assess the types and scope of first aid for pelvic injuries in women in conditions of local military conflict.   MATERIAL AND METHODS. To achieve this goal, an analysis of injuries received during local military operations carried out in the Republic of Chechnya from 1991 to 2000 was carried out. The treatment was carried out on the basis of the surgical hospital of medical organization No. 9 in Grozny. The severity of the injury was determined retrospectively using the Field Surgery Scale, distinguishing four degrees of severity. Injured patients with combined injuries to the chest, abdomen, and head were excluded. The average age of patients was 34 [28; 40] years. The total number was 86.   RESULTS. As the study shows, group A included 54 (62.8 %), and group B included 32 (37.2 %) patients. The distribution by group is presented as follows: in group A, 44 (51.2 %) shrapnel wounds, 10 (11.6 %) gunshot wounds. In group B, there were, respectively, 25 shrapnel (29.1 %) and 7 gunshot (8.1 %) wounds. Further analysis showed that penetrating wounds predominated, which were observed in 67 (77.9 %) cases, non-penetrating wounds were only revealed in 19 (22.1 %) cases (r = 0.97, p < 0.05, statistically significant). Distribution by groups: in group A there were 48 (55.8 %) and 6 (7.0 %), respectively, in group B there were 19 (22.1 %) and 13 (15.1 %) observations. Anti-shock measures, which include pain relief and infusion therapy, were carried out in 31 (36.0 %) cases in group A and in 5 (5.8 %) cases in group B (r = 0.97, p < 0 .05, statistically significant). At the same time, in the group of patients where first aid was provided by random witnesses or as self-help, the n